Effects of carbon-fiber plate design on foot stress injury risk: a finite element analysis - Guan, Linlin; Guo, Yangyu; Wang, Haichun; Wu, Yusen; Jia, Yunlong; Zhu, Xiaolan (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionCarbon-fiber plate (CFP) running shoes may alter ankle and foot biomechanical loading patterns, thereby potentially increasing the risk of foot stress injuries. However, there still a lack of systematic quantitative analysis of how multiple key design parameters (determining CFP performance) influence foot biomechanical responses. This study aimed to clarify how composite CFP influence the mechanical response of the foot and ankle, with the goal of reducing overuse injuries and providing biomechanical guidance for the structural design of CFP running shoes.MethodsA three-dimensional finite element (FE) model of the foot–CFP running shoes system was developed to analyze the effects of plate thickness (1.0, 1.25, and 1.5 mm), weaving type (Unidirectional carbon fiber (UD)/Woven carbon fiber (WO)), and ply angle (±30°, ±45°, and ±60°) on foot stress and midsole mechanical behavior.ResultsThe results showed that CFP thickness was positively related to midsole stiffness. Plantar stress first decreased and then increased with increasing plate thickness. A thicker plate reduced the peak metatarsal stress and led to a more even stress distribution across the forefoot. At the same thickness, UD plate with smaller ply angles lowered metatarsal loading, while WO plate with moderate angles also helped reduce stress concentration.ConclusionDuring long-distance running, the thicker UD plate with a small ply angle exhibits greater potential for reducing loads on the metatarsals and plantar soft tissues, while the WO plate with moderate ply angle provides a more balanced load distribution. From the perspective of injury-risk reduction, the latter may be more favorable for recreational runners.